A prospective study of demographic and socioeconomic factors responsible for non-acceptance of family planning methods at tertiary care teaching hospital, Gujarat, Indiaal, Gujarat, India - Joharwal, Neelam; Kapadia, Shital (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Population explosion has been major challenge for India since Independence. The adoption of contraceptive methods remains the best solution to this problem. The objective of this study was to determine the factors for non-acceptance of different contraceptive methods among married women of postnatal ward in tertiary care hospital, Ahmedabad, Gujarat, India. The aim of the study was to analyse about the level of awareness and attitude towards different methods of contraception among married women of reproductive age groups. Methods: It was a prospective observational study carried out in the department of obstetrics and gynaecology, B. J. Medical College, Civil Hospital, Ahmedabad, Gujarat, India, a tertiary care teaching hospital from June 2019 to November 2020. 200 patients meeting inclusion criteria were included. Case sheets were analysed to obtain data regarding reasons for non-acceptance of contraceptive methods. Results: In our study, we found that among study population 64% women use family planning methods, which was still low as compared to developed countries. 36% women were non-users in study population. The main reason of non-acceptance of contraceptive method were desire for male child, non-allowance by religion/custom, the myth regarding price of contraceptive method, desire of more children and worry about side effects. Conclusions: To increase the use of contraceptive among women, we can increase awareness about different family planning method with counselling about various available contraceptives. It is also important to increase participation of husbands as they often influence the decision regarding reproductive health of women.